2007
DOI: 10.1017/s0790966700010375
|View full text |Cite
|
Sign up to set email alerts
|

A needs analysis for the provision of a speech and language therapy service to adults with mental health disorders

Abstract: Objectives: To examine a sample of adults with mental health disorders attending at an area psychiatric service, for the presence of impairments in language, communication and swallowing, using a test battery administered by speech and language therapists.Method: The study surveyed a randomly selected sample (n = 60) of patients from an acute psychiatric inpatient unit and associated community services, using several standardised measures of language, communication and swallowing.Results: On this test battery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Neither dysphagia frequency outcome nor dysphagia intervention outcome documented [55] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented [56] Describes gastro-oesophageal disorders only [57] Single-case studies [58] Review article including 2 single case studies [59] Outcomes for general population (not limited to population of interest) [60] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented [61] Single case study [62] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented [63] Single case study [64] Letter to the editor [65] Single case study [66] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented [67] Letter to the editor [68] Letter to the editor [69] Letter to the editor with single case study [70] Letter to the editor [71] Letter to the editor with single case study [72] Commentary [73] Letter to the editor [74] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented Provides proportion of psychiatric hospital deaths attributed to choking. [75] Duplicate data presented in [6] which has been included in this review [76] Letter to the editor [77] Single case study [78] Letter to the editor [79] Single case studies [80] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented [81] Neither dysphagia frequency outcome nor dysphagia intervention outcome in the specified population documented [82] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented…”
Section: Discussionmentioning
confidence: 99%
“…Neither dysphagia frequency outcome nor dysphagia intervention outcome documented [55] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented [56] Describes gastro-oesophageal disorders only [57] Single-case studies [58] Review article including 2 single case studies [59] Outcomes for general population (not limited to population of interest) [60] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented [61] Single case study [62] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented [63] Single case study [64] Letter to the editor [65] Single case study [66] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented [67] Letter to the editor [68] Letter to the editor [69] Letter to the editor with single case study [70] Letter to the editor [71] Letter to the editor with single case study [72] Commentary [73] Letter to the editor [74] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented Provides proportion of psychiatric hospital deaths attributed to choking. [75] Duplicate data presented in [6] which has been included in this review [76] Letter to the editor [77] Single case study [78] Letter to the editor [79] Single case studies [80] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented [81] Neither dysphagia frequency outcome nor dysphagia intervention outcome in the specified population documented [82] Neither dysphagia frequency outcome nor dysphagia intervention outcome documented…”
Section: Discussionmentioning
confidence: 99%
“…In potential therapeutic interventions it can impact upon future recovery (Law et al 2007). One key Irish study demonstrated the importance of the need for specialist speech and language therapy assessment and support among adults with mental health problems in both community and inpatient settings (Walsh et al 2007). The authors argue that with the rise in 'talking therapies' and the growing evidence to support psychosocial approaches to mental health issues, opportunities have arisen for the increased participation of speech and language therapists (SLTs) in future treatment, intervention, and service developments.…”
Section: Speech and Language Education And Trainingmentioning
confidence: 99%
“…For people with mental health conditions and/or intellectual disabilities (IDs) the experience of swallowing difficulty is often exacerbated by other mealtime stresses from psychological, behavioural, social or environmental factors (Ball et al , 2012; Chadwick et al , 2003; Guthrie and Stansfield, 2017). The prevalence of dysphagia in adults with mental health conditions has been the focus of recent reviews (Aldridge and Taylor, 2012; Cicala et al , 2019; Kulkarni et al , 2017b; Walsh et al , 2007) but this physical health issue remains an area of concern for this population due to lack of awareness, under-diagnosis and poor reporting of related incidents such as choking (Guthrie et al , 2015; Jones et al , 2008). The consequences for adults with dysphagia and mental health conditions who also have a diagnosis of IDs has been highlighted, with concerns raised around premature death from dysphagia related respiratory conditions and difficulties accessing diagnosis and treatment (Glover et al , 2017; Heslop et al , 2013).…”
Section: Introductionmentioning
confidence: 99%